2021
DOI: 10.4274/ejbh.galenos.2021.2021-1-4
|View full text |Cite|
|
Sign up to set email alerts
|

Breast Cancer Management During the COVID-19 Pandemic: The Senologic International Society Survey

Abstract: Objective: In early 2020, the spread of coronavirus disease-2019 led the World Health Organization to declare this disease a pandemic. Initial epidemiological data showed that patients with cancer were at high risk of developing severe forms of COVID-19. National scientific societies published recommendations modifying the patients' breast cancer (BC) management to preserve, in theory, quality oncologic care, avoiding the increased risk of contamination. The Senology International Society (SIS) decided to tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…People at risk of serious SARS-CoV-2 infections who require further examination or even hospitalization also present an increased risk for BC. Both diseases have common risk factors, such as advanced age, obesity, and type 2 diabetes (3,11,12). Chest scans performed as part of the diagnosis of COVID-19 infection are generally not accompanied by administration of iodized contrast, except when a pulmonary embolism is suspected, particularly in severe forms (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People at risk of serious SARS-CoV-2 infections who require further examination or even hospitalization also present an increased risk for BC. Both diseases have common risk factors, such as advanced age, obesity, and type 2 diabetes (3,11,12). Chest scans performed as part of the diagnosis of COVID-19 infection are generally not accompanied by administration of iodized contrast, except when a pulmonary embolism is suspected, particularly in severe forms (13).…”
Section: Discussionmentioning
confidence: 99%
“…The objective was twofold, not to result in a loss of chance from an oncological perspective, while protecting from a possible COVID-19 infection. The suspension of screening was one of these measures (2,3). Computed tomography (CT) scans, frequently performed in patients infected with SARS-CoV-2, have thus become one of the ways of detecting asymptomatic breast abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have shown that women with breast cancer have fewer severe forms of COVID-19 and less likely to die. 25,26 Regarding the oncologic treatment, when performing the step-by-step regression, it was detected that receiving treatment increased the odds of death. However, this effect was diluted upon inclusion on the multivariate analysis and variable adjustment.…”
Section: Survivalmentioning
confidence: 99%
“…People at risk of serious SARS-CoV-2 infections who require further examination or even hospitalization also present an increased risk for BC. Both diseases have common risk factors such as advanced age, obesity, and type 2 diabetes (3,11,12). Chest scans performed as part of the COVID-19 infection check-up are generally not accompanied by administration of iodized contrast except when a pulmonary embolism is suspected, particularly in severe forms (13).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…The objective was twofold, not to result in a loss of chance from an oncological perspective, while protecting from a possible COVID-19 infection. The suspension of screening was one of these measures (2,3). Computed tomography (CT) scans frequently performed in patients infected with SARS-CoV-2 infections have thus become one of the ways of detecting asymptomatic breast abnormalities.…”
Section: Introductionmentioning
confidence: 99%